2020
DOI: 10.2174/1568026620666200211110545
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Personality, Depression, Anxiety and Cognition to Understand Early Stage of Alzheimer’s Disease

Abstract: The multifaceted nature of Alzheimer’s disease (AD) and Mild cognitive impairment (MCI) can lead to wide inter-individual differences in disease manifestation in terms of brain pathology and cognition. The lack of understanding of phenotypic diversity in AD arises from a difficulty in understanding the integration of different levels of network organization (i.e. genes, neurons, synapses, anatomical regions, functions) and in inclusion of other information such as neuropsychiatric characteristics, personal his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…Patients with early-onset AD are more likely to develop depression than those with late-onset AD due to significant changes in lifestyle, roles, and responsibilities, as well as poor social adaptability ( 43 ). More and more studies have shown that depression not only accelerates the rate of cognitive decline and affects the quality of life but also increases mortality and suicide rates in AD patients ( 44 ). Seriously, patients with Alzheimer’s disease whose depressive symptoms are the first to occur are prone to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with early-onset AD are more likely to develop depression than those with late-onset AD due to significant changes in lifestyle, roles, and responsibilities, as well as poor social adaptability ( 43 ). More and more studies have shown that depression not only accelerates the rate of cognitive decline and affects the quality of life but also increases mortality and suicide rates in AD patients ( 44 ). Seriously, patients with Alzheimer’s disease whose depressive symptoms are the first to occur are prone to misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…64 In fact, this may be the case of the observed negative effect of increased blood cholesterol levels on midlife cognition, which based on previous studies may associate with cognitive decline in later life. 65 The association between anxiety and depressive symptoms and cognitive decline 66,67 in the healthy elderly [68][69][70] and presymptomatic stages of cognitive disorders [71][72][73] is well documented. We here extend…”
Section: Midlife Cognition Interpretedmentioning
confidence: 99%
“…The association between anxiety and depressive symptoms and cognitive decline 66,67 in the healthy elderly 68–70 and presymptomatic stages of cognitive disorders 71–73 is well documented. We here extend these observations by showing that anxiety and depressive symptoms influence physiological cognition already in midlife and by identifying personality traits such as hostility and type D personality in addition to quality of life as variables negatively influencing physiological cognition.…”
Section: Narrativementioning
confidence: 99%
“…BZD users are more likely to experience depression and anxiety than the non-users (25). However, depression and anxiety can significantly affect cognitive test performance, confounding the result of the study (26). To reduce the influence of depression and anxiety on the cognition results in this study, participants with moderate symptoms of anxiety or depression, reflected by scores of SAS score of ≥20 and GDS scores of ≥15, respectively, were excluded.…”
Section: Screeningmentioning
confidence: 99%
“…However, some research showed that aged BZD users suffered more cognitive impairment as their time on the drug increased (51,(55)(56)(57). These inconsistencies may be due to researchers not considering that BZD users had higher levels of anxiety than the control group, which results in a reduction in cognitive functioning (26). This explanation is supported by the research of Lucki et al, which reported that the cognitive performance of long-term BZD users did not differ significantly from that of non-users after matching for age, gender, education, and anxiety levels (58).…”
Section: Bzd Using Time and The Cognition Decline In Highly Educated mentioning
confidence: 99%